Measuring the Quality of Service of Nadjem magra football Club in M'sila using SERVSPORT - SAIDANE, SAAD (Université de M'sila, 2019)
In this research, We have used the ServeSport to measure the quality of service at the Nadjem Magra Football Club. Depending on the descriptive and analytical approach to his relevance to the nature of the research. There are a lot of international standards that measure the quality of service in various fields, among them is the ServeSport scale, which measures the quality of service in sports. In this research, the study community are the players , coaches and managers Nadjem Magra Football Club in M'sila. A comprehensive inventory sample was adopted to target as many individuals as possible. We have used the ServeSport dimensions questionnaire as a data collection tool. The second part of the questionnaire is answered using the five-degree Likert scale. Respondents were asked to give a grade on whether or not they agreed with each of the terms. The most important results are: -The Nadjem Magra football Club has significant indicators of the quality of service provided in relation to the facilities, safety and reliability, financial aspects, response and empathy. - Nadjem Magra Football Club has no significant indicators of the quality of service provided in relation to the physical aspects.